2022
DOI: 10.3390/vetsci9100554
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Regarding Dog Euthanasia and Causes of Death at a Veterinary Teaching Hospital in Italy: Preliminary Results

Abstract: The decision to request and proceed with euthanasia in a dog is complex and predictors of such decisions are important. This study investigates the risk factors (demographic and clinical) associated with the main clinical causes and methods of death (euthanasia or unassisted death) in a population of dogs. By comparing euthanasia to unassisted deaths, the authors assess causes of death to evaluate their relative impacts on decision-making to choose euthanasia compared with an unassisted death. For this, goal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In analyzing the trend over the last thirty years, the results have shown evidence of a substantial increase. In recent years, there has been a great focus on mortality and longevity in canine populations [5,[7][8][9]. The process of making decisions regarding euthanasia can pose a moral dilemma for veterinarians and evoke emotional distress for pet owners [1,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In analyzing the trend over the last thirty years, the results have shown evidence of a substantial increase. In recent years, there has been a great focus on mortality and longevity in canine populations [5,[7][8][9]. The process of making decisions regarding euthanasia can pose a moral dilemma for veterinarians and evoke emotional distress for pet owners [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Data extracted from electronic clinical records included breed, age, gender (male/female), neuter status, manner of death [euthanasia (E), unassisted (UD) or accidental (AD)], and cause of death, categorized into one of the following six physiopathological processes (PPs) [5]: infectious/inflammatory conditions, degenerative diseases, neoplastic processes, toxins, traumatic events, and other (including congenital diseases, metabolic disorders, and vascular diseases).…”
Section: Data Collection and Study Populationmentioning
confidence: 99%
“…In the case of animals with cardiovascular, renal, hepatic, neurologic, and cancer diseases where the treatment is no longer providing adequate results, there are ethics questions regarding whether it is correct to extend the suffering of an animal, and until which point. A comparative study conducted by Pugliese et al [ 34 ] evaluated the causes that led guardians to choose euthanasia in comparison to an unassisted death. They found that 40.7% and 50.8% of the cases were due to euthanasia and unassisted deaths, respectively.…”
Section: Ethical Implications Of Euthanasia In Companion Animalsmentioning
confidence: 99%
“…Problem behaviors that increase the risk of harm or decrease welfare for the dog or others around them may result in euthanasia of the dog, despite the dog being physically healthy ( 41 , 42 ). This is commonly known as behavioral euthanasia (BE).…”
Section: Introductionmentioning
confidence: 99%